PHYTOCHEMICAL, PHYSICOCHEMICAL AND ANTIOXIDANT SCREENING OF OIL EXPRESSED FROM SEEDS OF ADANSONIA DIGITATA L. A VALUABLE PHARMACEUTICAL, NUTRACEUTICAL AND COSMECEUTICAL PLANT. - Ijaz Ali; Muhammad Muzammil Ramzan; Muhammad Abdul Haq Khan; Irfana Lalarukh; Haseeb Ahmad Saeed; Umbreen Farrukh; Summan; Muhammad Umar; Syed Faizan Abbas Naqvi; Syeda Faiqa Ijaz; Hassan Farooq Ahmad Khan; Umar Farooq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Human beings have been gaining benefits from plants since prehistoric times. Plants bestow us with many ways. In recent years, extensive research on plants has been carried out, including pharmaceutical, nutraceutical, and cosmetic aspects. Hence, collaborative and multidisciplinary efforts are needed. Exploration of phytochemical and physicochemical parameters of a plant species enhances its better understanding. This research is aimed at investigation of oil expressed from seeds of Adansonia digitata L., a multi-purpose tree. Phytochemical, physicochemical, and bioactive investigations have been carried out. Such investigations can help to evaluate the traditional claims and folkloric use of baobab seed oil. Oil is traditionally used for cosmetic purposes. It is applied for skin health. It is also used for treatment of hair fall and for growing healthy and long hair. The kernels are rich in fat. The whole seeds and the kernels have relatively high lipid content. Oleic acid was present with the highest area percentage (115.4), following linoleic acids (79.5) as major fatty acids, whereas others include palmitic acid (33.4) and stearic acid (14.75). Eight compounds belonging to various chemical classes were screened. These compounds exhibit significant pharmaceutical, nutraceutical, and cosmeceutical values. The antioxidant effect of the seed content was found to be very high (91.187%). These findings give a clear indication of the use of this oil as multipurpose oil.